Analytic Kantianism: Sellars and McDowell on Sensory Consciousness - Haag, Johannes (Con-Textos Kantianos. International Journal of Philosophy, 2017)
Wilfrid Sellars and John McDowell can both be read as proponents of Analytic Kantianism. However, their accounts differ in important detail. In particular, McDowell has criticized Sellars’s account of sensory consciousness in a number of papers (most notably in LFI and SC), both as a reading of Kant and on its systematic merits. The present paper offers a detailed analysis of this criticism and a defense of Sellars’s position against the background of a methodology of transcendental philosophy.
Keywords: Kant; Sellars; McDowell; Transcendental Philosophy; perception; intuition; judgment